Refined reconstruction of liquid–gas interface structures for stratified two-phase flow using wire-mesh sensor. (December 2015) - Schleicher, Eckhard; Besim Aydin, Tayfun; Vieira, Ronald E.; Torres, Carlos F.; Pereyra, Eduardo; Sarica, Cem; Hampel, Uwe
Abstract: Wire-mesh sensors (WMS), developed at HZDR[13, 4], are widely used to visualize two-phase flows and measure flow parameters, such as phase fraction distributions or gas phase velocities quantitatively and with a very high temporal resolution. They have been extensively applied to a wide range of two-phase gas–liquid flow problems with conducting and non-conducting liquids. However, for very low liquid loadings, the state of the art data analysis algorithms for WMS data suffer from the comparably low spatial resolution of measurements and from boundary effects, caused by e.g. flange rings – especially in the case of capacitance type WMS. In the recent past, diverse studies have been performed on two-phase liquid–gas stratified flow with low liquid loading conditions in horizontal pipes at the University of Tulsa. These tests cover oil–air flow in a 6-inch ID pipe and water–air flow in a 3-inch ID pipe employing dual WMS with 32×32 and 16×16 wires, respectively. For oil–air flow experiments, the superficial liquid and gas velocities vary between 9.2 m/s≤ ν SG ≤15 m/s and 0.01 m/s≤ ν SL ≤0.02 m/s, respectively [2]. In water–air experiments, the superficial liquid and gas velocities vary between 9.1 m/s≤ ν SG ≤33.5 m/s and 0.03 m/s≤ ν SL ≤0.2 m/s, respectively[17, 18] . In order to understand the stratified wavy structure of the flow, the reconstruction of the liquid–gas interface is essential. Due to the relatively low spatial resolution in the WMS measurements of approximately 5 mm, the liquid–gas interface recognition has always an unknown uncertainty level. In this work, a novel algorithm for refined liquid–gas interface reconstruction is introduced for flow conditions where entrainment is negligible. Highlights: Stratified-wavy oil-air and water air two-phase flows are studied. Liquid gas interface is reconstructed based on wire-mesh sensor data. The details of the interface are visualized after the refinement of the data. The interpolation used in the mesh refinement conserves the measured liquid holdup.